(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
this article presents the technology for organizing experimental work aimed at developing and enhancing communication skills for students in the field of road engineering education. The main goal of the research is to develop communication, expression of ideas, and teamwork skills—key components of professional competence for future engineers—through the use of modern technologies in the educational process